Drinking male tears: language, the manosphere, and networked harassment. Issue 4 (4th July 2018) - Marwick, Alice E.; Caplan, Robyn
Abstract: While popular discourse often frames online harassment as an issue of individuals engaged in abhorrent behavior, harassing behavior is often networked in that it is coordinated and organized. When feminists and female public figures experience harassment, it often originates from members of a loose online network known as the manosphere, a set of blogs, podcasts, and forums comprised of pickup artists, men's rights activists, anti-feminists, and fringe groups. While the particular beliefs of these groups may differ, many participants have adopted a common language. This paper explores the discourse of the manosphere and its links to online misogyny and harassment. Using critical discourse analysis, we examine the term misandry, which originates in the manosphere; trace its infiltration into more mainstream circles; and analyze its ideological and community-building functions. We pay particular attention to how this vocabulary reinforces a misogynistic ontology which paints feminism as a man-hating movement which victimizes men and boys.